STRUCTURE FUNCTIONAL STATE OF DAMAGED SPLEEN IN CHILDREN AFTER NONOPERATIVE TREATMENT - V. V. Podkamenev; I. A. Pikalo; T. M. Andaeva; T. N. Boiko (Вестник хирургии имени И.И. Грекова)
The results of treatment of 75 children with spleen damage were studied. The conservative treatment was applied in 69 (92%) cases. A restoration of spleen structure was noted in case of spleen injury on 3-4 weeks. The complete normalization of the spleen structure occurred in terms of 3-4 months after trauma. Posttraumatic cysts appeared in case of large defects and hematomas after 2-3 weeks and disappeared by 5-6 months. The regenerative process of shallow ruptures was registered after 3-10 weeks, but the deep ruptures were healed after 6-30 weeks. The preservation of the spleen after trauma have led to structure and function recovery and could be considered as primary prevention of asplenism.